Substrate moisture and temperature in the germination and vigor of pitaya - Oliveira Júnior, Jair Lucas; Almeida Neta, Maria Nilfa; Santos de Souza David, Andréia Márcia; de Aguiar, Ana Cecília Mariana; Oliveira Gomes, Anderson Gustavo; Ribeiro Amaro, Hugo Tiago; Silva Donato, Luan Mateus (Comunicata Scientiae, 2015)
Knowledge of appropriate conditions of water and temperature is very important for the metabolic activities involved in the germination process. However, the Rules for Testing Seeds do not indicate the volume of water and the ideal temperature for pitaya germination. The study was carried out to evaluate different water volumes in the substrate and temperatures on seeds germination and vigor of pitaya. The experimental design was completely randomized in a factorial 5 x 3, with treatments consisted of five water volumes in the substrate and three temperatures. The used water volumes was equivalent to 1.5; 2.0; 2.5; 3.0 and 3.5 times the dry weight of the substrate. Were tested at constant temperatures of 20, 25 and 30 °C. The parameters evaluated were: germination, first count of germination, emergence speed index, length and dry mass of plantlets. The temperature of 25 °C and a water volume in the range of 2.5 to 3.5 times the weight of substrate is the most suitable combination for doing germination tests and evaluating the vigor of pitaya seeds. The temperature of 20 °C and the volume of water 1.5 times the weight of the substrate inhibited germination of seeds